2009
DOI: 10.1007/s12072-009-9131-4
|View full text |Cite
|
Sign up to set email alerts
|

Diffuse intrahepatic recurrence after percutaneous radiofrequency ablation for solitary and small hepatocellular carcinoma

Abstract: Two patients developed segmental, diffuse intrahepatic recurrence after percutaneous radiofrequency ablation (RFA) to treat a primary, solitary, and small (2.5 cm) hepatocellular carcinoma (HCC). Despite the size of the HCC, levels of the tumor markers (α-fetoprotein, α-fetoprotein-L3%, and des-γ-carboxyprothrombin) were all elevated before RFA, and tumors in both patients were contiguous with a major branch of the portal vein. Tumor biopsies of both patients revealed moderately differentiated HCC but diagnost… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
47
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 44 publications
(47 citation statements)
references
References 31 publications
(30 reference statements)
0
47
0
Order By: Relevance
“…However, the guidelines do not address tumor differentiation. Some previous studies have shown that RFA, which is used to treat poorly differentiated HCC, is associated with a risk of tumor seeding and diffuse intrahepatic recurrence . Despite this, it remains unclear as to whether or not tumor differentiation is actually associated with prognosis.…”
Section: Introductionmentioning
confidence: 99%
“…However, the guidelines do not address tumor differentiation. Some previous studies have shown that RFA, which is used to treat poorly differentiated HCC, is associated with a risk of tumor seeding and diffuse intrahepatic recurrence . Despite this, it remains unclear as to whether or not tumor differentiation is actually associated with prognosis.…”
Section: Introductionmentioning
confidence: 99%
“…Of the local therapies, radiofrequency ablation (RFA) is more curative than percutaneous ethanol injection, but prognosis-related issues, such as dissemination, recurrence accompanied by portal invasion, and aggressive recurrence after RFA, have been identified [12][13][14][15], and histologically poorly differentiated HCCs have been reported to be a risk factor for dissemination [16]. Since there is a high possibility that poorly differentiated HCCs, even if small, may be advanced, with vascular invasion or intrahepatic metastasis, complete cure cannot be obtained by local therapy alone, and there is a risk that such treatment may cause metastasis or dissemination [16][17][18]. Because it is extremely difficult to diagnose tiny microscopic vascular invasion or intrahepatic metastases on diagnostic imaging, it will be extremely important in the future to diagnose poorly differentiated HCCs, which have higher malignant potential, to plan the treatment of HCCs.…”
Section: Introductionmentioning
confidence: 99%
“…There have been various terminologies used in previous studies and case reports representing the phenomenon of aggressive tumor recurrence after RFA for HCC, such as “rapid intra-hepatic dissemination” [9], “aggressive recurrence” [10,11], “scattered and rapid intrahepatic recurrence” [12], “early diffuse recurrence” [13], “diffuse intrahepatic recurrence” [14], “rapid aggressive tumor progression” [15], and “aggressive intrasegmental recurrence” [8]. Among these terminologies, we restricted our search to publications that included a definition of tumor recurrences.…”
Section: Definition Of Aggressive Tumor Recurrencementioning
confidence: 99%
“…1). Another hypothesis is that rapid heating of a tumor may lead to a sudden increase in internal pressure of ablated tissue and cause the scattering of malignant cells around the ablation zone [14,18]. In addition, although the results were based on an animal model studies, Ahmed et al [19] recently reported that RFA of normal liver tissue can stimulate distant tumor growth mediated by the hepatocyte growth factor/c-Met pathway and vascular endothelial growth factor activation.…”
Section: Mechanism Of Aggressive Tumor Recurrencementioning
confidence: 99%
See 1 more Smart Citation